Psychophysiological possibility of mountaineers and climbers specializing in speed climbing and climbing difficulty - Zh.L. Kozina; O.A. Ryepko; Kr. Prusik; Mirosława Cieślicka (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The purpose of this study was comparative characterization of psycho-physiological features of elite athletes the representatives of the climbing on the complexity, speed and climbers. The study included 26 elite athletes (age 19-22 years). It is shown that athletes much more accurately reproduce a time interval of 30 seconds, compared with a time interval of 1 minute. Revealed that the climbers (climbing speed) and in some cases, climbers (climbing difficulty)show significantly better results on tests of reaction rate under difficult conditions. Found higher rates of mobility and strength of nervous processes in rock climbers compared with climbers. This fact is related to the specific training and competitive activities of climbing, which requires a global concentration or under conditions of maximum circa power voltage.